Acute Abdominal Injuries in Sports: Review and Management Recommendations - Bartosiński, Ryszard; Szustak, Jan; Wijata, Anna; Przybyłek-Stępień, Zuzanna; Dutkiewicz, Justyna; Mączyńska, Wiktoria; Kąpa, Maria; Szepietowski, Bartosz; Kaźmierczak, Jakub; Wijata, Michał; Rycerz, Ewelina; Pasek, Piotr (Quality in Sport, 2025)
Acute abdominal injuries in sports pose diagnostic and therapeutic challenges, requiring rapid intervention. This article reviews their mechanisms, symptoms, and management based on literature analysis. The most common injuries include solid organ damage, hollow organ perforations, and hemorrhages. Imaging, particularly FAST ultrasonography and computed tomography, plays a key role in assessing injury severity and guiding treatment, which ranges from conservative management to surgery. Early recognition of life-threatening conditions like internal hemorrhage or peritoneal signs is crucial, as they may be difficult to detect without specialized diagnostics. The paper discusses the epidemiology, mechanisms, and clinical characteristics of these injuries, highlighting ultrasound in the FAST protocol as a key diagnostic tool. Treatment recommendations consider the role of medical support during training and competition. The authors stress the importance of medical education for coaches, athletes, physiotherapists, and medical staff to enhance risk awareness and improve preventive and interventional measures. The article aims to increase awareness among sports medicine professionals, surgeons, emergency personnel, and sports staff, ultimately improving treatment outcomes through proper training and diagnostic access.